Differences in postural disturbances between female adolescents handball players and nontraining peers - Jandric, Slavica Dj (Vojnosanitetski pregled, 2017)
Background/Aim. Physical activity and sport can influence the extent of the presence of the postural disturbances in children. The aim of this study was to investigate the occurrence of differences in the postural disturbances in female adolescents in relation to team handball training. Methods. This investigation involved 150 female adolescents with the average age of 13.2 ± 1.34 years divided into two groups (50 adolescents trained handball and 100 did non train it). Results. The study determined a statistically significant difference in the total number of postural disturbances between the two groups of adolescents (p < 0.001). The presence of the flat foot was statistically significantly higher in untrained adolescents (p < 0.001), but the presence of the scoliosis, kyphosis, lordosis, and pes varus was not found (p > 0.05). Conclusion. Handball adolescents players have less postural disturbances than untrained adolescents. Flat foot is significantly less frequent in female adolescents handball players than in untrained ones. Findings obtained in this investigation can help us in planning continuous prevention, observation and care for untrained and trained team handball female adolescents with postural disturbances.